2005
DOI: 10.1681/asn.2004100836
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Renal Allograft Rejection by Urinary Monokine Induced by IFN-γ (MIG)

Abstract: Early diagnosis of acute allograft rejection (AR) is still decisive for long-term renal allograft survival. The aim of this study was to define the role of the chemokine monokine induced by IFN-␥ (MIG) (CXCL9) and IFN-␥-inducible protein 10 (IP-10) (CXCL10) as early markers of AR in renal transplantation (NTX). In a prospective study, 69 de novo renal transplant recipients were monitored and urine samples were collected after NTX for a median of 29 d. In pH-adjusted urine, MIG and IP-10 were determined by modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
77
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 36 publications
10
77
0
4
Order By: Relevance
“…Suthanthiran et al 2 recently showed that the urinary cell mRNA profile can serve as a diagnostic and prognostic biomarker of TCMR. Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells.…”
mentioning
confidence: 99%
“…Suthanthiran et al 2 recently showed that the urinary cell mRNA profile can serve as a diagnostic and prognostic biomarker of TCMR. Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells.…”
mentioning
confidence: 99%
“…Nas biópsias renais, houve aumento da expressão de MIG/CXCL9 em gloméru-los, túbulos e células infiltrativas. 55 Hauser et al 56 verificaram, em 15 pacientes com RA dentro de um grupo de 69 transplantados renais, que a dosagem de MIG/CXCL9 e IP-10/CXCL10 em amostras únicas de urina permitia a predição de RA, assim como de resposta ao tratamento. MIG/CXCL9 apresentou maior sensibilidade (93,3%) e especificidade (89%) para RA, com boa correlação com IP-10/CXCL10 (p < 0,01), e não se alterou em presença de NTA.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified
“…MIG/CXCL9 apresentou maior sensibilidade (93,3%) e especificidade (89%) para RA, com boa correlação com IP-10/CXCL10 (p < 0,01), e não se alterou em presença de NTA. 56 O aumento dessas citocinas ocorreu de 2 a 3 dias antes do aumento da creatinina e 6 a 7 dias antes do diagnóstico histopatológico de RA. 56 Matz et al 57 acompanharam 35 transplantados renais por 6 meses e mostraram que a medida do RNA mensageiro para IP-10/CXCL10 urinário no primeiro mês pós-transplante apresentava sensibilidade de 58% e especificidade de 75% para predizer a função renal medida 3 e 6 meses após o transplante.…”
Section: Citocinas E Quimiocinas No Tecido Renal E No Sangue De Transunclassified
See 2 more Smart Citations